Evaluation of the potentialities of the essential oil of Ocimum gratissimum Linn. towards environmental and industrial perspectives through microbial exploitation. - Giri, Pranab (Current Botany, 2017)
Nature has its own machinery to regulate spontaneous interaction between biotic and abiotic factors of its own to provide back up for self stability and sustainability. The plant microbe interaction is a biotic interaction the resultant of which has immense role to resolve different environmental issues. It also has some fruitful effect for welfare of human beings. The present article deals with at what extent the biotic interaction between the essential oil from Ocimum gratissimum and microbial resources from the natural environment could be exploited in respect of environmental as well as industrial perspectives.